Issues Related to Wisconsin "Failure to Pay Forfeitures" Driver's License Suspensions - (:unkn) unknown (My University, 2014)
This paper examines the compounding problems resulting from court-ordered removal of driving privileges for low-income residents in Milwaukee County and Wisconsin as a “tool” for spurring payments of municipal fines, forfeitures and fees (including charges for violations unrelated to dangerous driving). The analysis is based on data from the Wisconsin Department of Transportation Division of Motor Vehicles, the Milwaukee County Sheriff’s Office, and Branch A of the Milwaukee Municipal Court (i.e., handling municipal cases incarcerated in county jail). Police and court actions taken in Ferguson, Missouri, brought national attention to one suburban municipality’s routine use of traffic stops, arrest warrants, debtors’ jail, and racial targeting. This study considers race, class and criminal justice consequences of suspending driver’s licenses as a debt collection tool in Wisconsin where the barring of driving privileges based on FPF/FPJ (“failure to pay forfeitures” and “failure to pay forfeitures-juveniles”) suspensions falls most heavily on men and boys of color and residents in lower-income Milwaukee zipcodes.
Keywords: driver's license; criminal justice; discrimination; poverty